Innovative Technologies, Nanoprivates and Methods of Application of Probiotics in Veterinary Pharmaceuticals - Mengatova Xurshida Toshmuxamatovna,; Anorova Ruxsora Jumabek qizi, (American Journal of Biomedicine and Pharmacy, 2026)
This article presents information on modern innovative technologies in veterinary pharmacy, in particular nanopreparations and probiotics. The role of nanotechnology in drug delivery systems, the importance of probiotics in improving animal health and productivity are scientifically analyzed. The article reviews the effectiveness and prospects of innovative drugs used for various animals (cattle, poultry, pigs, fish).